(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Non-communicable diseases (NCDs) like diabetes and cardiovascular diseases(CVDs) are significant health challenges worldwide, particularly in Uzbekistan. Thisarticle reviews the current landscape of NCDs, focusing on diabetes and CVDs, in Uzbekistan. It discusses the prevalence, risk factors, and challenges in diagnosis andtreatment. The article highlights the importance of early identification andmanagement of these diseases, and proposes strategies for their prevention and control in Uzbekistan.